Symbolic Convergence or Divergence? Making Sense of (the Rhetorical) Senses of a University-Wide Organizational Change - Ba, Lina; Zhao, W. G. Will (Frontiers in Psychology, 2021)
This research investigates the extent to which organizational change initiatives may lead to divergent patterns of sensemaking among organizational members. Drawing on the Symbolic Convergence Theory, we performed an in-depth Fantasy Theme Analysis of organization members' rhetoric around an organizational change at a private university. Our analysis uncovers six fantasy themes and two corresponding fantasy types, which lead to no rhetorical vision. The lack of cognitive convergence between change initiators and change recipients suggests the inherent incompatibility between managerial and employee fantasies around organizational change, barring the exceptions of dual-responsibility change recipients (e.g., faculty members who also assume administrative responsibilities) tend to adopt the change initiator rhetoric. Overall, this study informs our extant knowledge of change sensemaking with novel theoretical and methodological insights and bears implications for organizational change researchers and practitioners alike.